Reservas lipídicas corporais em Pratylenchus brachyurus e Meloidogyne incognita - Pinto, Giselle Batista (2017)
Phytonematodes cause damage to crops and economic losses in agriculture worldwide. There are several species of phytonematodes in innumerous genera that are important for agricultural production, but in this work we focused on two species of two important genera: Meloidogyne incognita and Pratylenchus brachyurus. The species studied in this work are highly relevant due to the wide range of hosts and the wide geographic distribution in regions of agricultural importance. Understanding the processes involved in the development and survival of these nematodes is needed to search for new management strategies. Body energy is an essential factor in the development of nematodes because it is related to their survival, penetration and reproduction. The body energy in nematodes may come from carbohydrates (trehalose and glycogen) and lipids (triglycerides and neutral lipids). Among these sources, neutral lipids are considered the most important. The objective of this study was to investigate the body lipid content through the use of a dye that has affinity to lipids. The relationship between the colored body lipid area and the infectivity in maize roots was studied for the species P. brachyurus.